2019
DOI: 10.3390/jcm8111945
|View full text |Cite
|
Sign up to set email alerts
|

Conversion Surgery for Advanced Pancreatic Cancer

Abstract: While primarily unresectable locally advanced pancreatic cancer (LAPC) used to be an indication for palliative therapy, a strategy of neoadjuvant therapy (NAT) and conversion surgery is being increasingly used after more effective chemotherapy regimens have become available for pancreatic ductal adenocarcinoma. While high-level evidence from prospective studies is still sparse, several large retrospective studies have recently reported their experience with NAT and conversion surgery for LAPC. This review aims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 98 publications
(143 reference statements)
0
19
1
1
Order By: Relevance
“…A previous study revealed that the median waiting time for HCCA surgery was 74 days, which did not impact resectability, metastasis, tumor stage or survival [ 38 ]. Consistent with this conclusion, we suggest evaluating borderline HCCA patients receiving preoperative neoadjuvant therapy, similar to the evaluation process for pancreatic cancer patients [ 39 ]. These noninvasive methods could downstage and evaluate the sensitivity of chemotherapy, which assists in evaluating surgical necessity and reducing the number of senseless exploration procedures.…”
Section: Discussionmentioning
confidence: 65%
“…A previous study revealed that the median waiting time for HCCA surgery was 74 days, which did not impact resectability, metastasis, tumor stage or survival [ 38 ]. Consistent with this conclusion, we suggest evaluating borderline HCCA patients receiving preoperative neoadjuvant therapy, similar to the evaluation process for pancreatic cancer patients [ 39 ]. These noninvasive methods could downstage and evaluate the sensitivity of chemotherapy, which assists in evaluating surgical necessity and reducing the number of senseless exploration procedures.…”
Section: Discussionmentioning
confidence: 65%
“…Instead, local resectability can only be assessed by surgical exploration, with frozen section biopsies. If the frozen biopsy reveals a persistent true invasion of a major artery, surgical resection can be abandoned, or the decision for an arterial resection must be made [22]. In our case, however, a preoperative CT revealed that the tumor had shrunk to 18 × 7 mm in diameter with encasement of the CHA, so the findings of UR-LA pancreatic cancer remained, and intraoperative frozen section pathology findings confirmed tumorfree margins.…”
Section: Discussionmentioning
confidence: 69%
“…Für Patienten mit resektablem und Borderline-resektablem Pankreaskarzinom kann auf Basis der aktuellen Datenlage eine primäre chirurgische Therapie empfohlen werden, wobei neoadjuvante Konzepte derzeit in randomisiert-kontrollierten Studien überprüft werden [ 17 ]. Lokal fortgeschrittene Pankreaskarzinome mit Infiltration oder Ummauerung der Arteria mesenterica superior oder des Truncus coeliacus sind per definitionem nicht resektabel und sollten daher mit einer neoadjuvanten Chemotherapie behandelt werden [ 18 ]. In der Praxis erfolgen die Beurteilung der Resektabilität und die Behandlungsallokation jedoch auch und gerade in interdisziplinären Tumorboards häufig auf der Grundlage persönlicher Erfahrungen und anhand nichtstandardisierter Parameter, sodass hier eine große Behandlungsheterogenität zu verzeichnen ist [ 19 ].…”
Section: Onkologische Resektion Und üBerlebenunclassified